Multimodal strategy for decreasing puerperal endometritis after vaginal delivery - Vera, Edy (2013)
Hospital infections are high when there is no adequate control of the multiple factors involved. During 2010 and part of 2011 rate of vaginal delivery puerperal endometritis rate was three times that of national standards. Therefore, we applied the World Health Organization (WHO)’s multimodal strategy intervention of hand washing that consists in 1) system change, 2) education and training, 3) feedback, 4) recalls, and 5) organizational climate. Objectives: To diminish puerperal endometritis rates in vaginal deliveries. Design: Quasi experimental, prospective a longitudinal study. Setting: Hospital Nacional Docente Madre Niño San Bartolome, Lima, Peru. Participants: Medical staff, residents, interns rotating in the delivery room. Interventions: Based on WHO Multimodal Strategy of hand washing. Main outcome measures: Rates of puerperal endometritis. Results: Puerperal endometritis started to decrease from 1.1% between 2010 and 2011 down to 0.7% between 2011 and 2012; this rate has been maintained almost constantly for over five months. Use of alcohol gel varied from 40 mL per month to 750 mL per month. Conclusions: Decrease of puerperal endometritis in vaginal deliveries was obtained by WHO Multimodal Strategy of hand washing intervention. Keywords: Hospital infections, puerperal endometritis, vaginal delivery, hand washing.